Utilizing Online History Learning Resources (Kitlv, Delpher Kranten and Beeldbank) in History Learning Class X SMA Negeri 3 Palu - Nuraedah Nuraedah; Charles Kapile; Fajar Nugroho (Engagement: Jurnal Pengabdian Kepada Masyarakat, 2022)
The use of online learning resources has a significant influence on student learning needs, especially with the distance learning system implemented at SMA Negeri 3 Palu, including the selection of student learning resources. The implementation of community service aims to provide knowledge to students in the context of utilizing online history learning resources KITLV, Delpher Kranten and Beeldbank in history learning class X SMA Negeri 3 Palu. This service activity was attended by history teachers and students, they were very enthusiastic in participating in the service activities. The resulting output is the knowledge of students and teachers regarding online learning resources that can be used for further learning activities.